Agronomic evaluation of a fertiliser with D-CODER technology, a new mechanism for the slow release of nutrients - Arrobas, Margarida (2013)
D-CODER is a fertilizer with a new slow-release mechanism consisting of an organomineral matrix that releases the nutrients only in the presence of growing plants. Pot and field experiments were carried out to study the release pattern of N from D-CODER. The experiments included grown and bare soil plots. The fertilizer treatments were DCODER, ammonium nitrate (ANpreplant), and the control. A fourth treatment was added to the cultivated plots, consisting of splitting the ammonium nitrate application of 25% at preplant and 75% as top-dressing (ANsplit). In the bare soil pots, 35 days after the fertilizer application (DAFA), NO3-N concentrations in the extracts of anion exchange membranes incubated in the soil for ANpreplant, D-CODER, and the control treatments were 118.5, 82.5 and 34.5 mg L-1, respectively, suggesting that part of N from D-CODER had not yet been released. In the pots cultivated with ryegrass, 209 DAFA, N recoveries for D-CODER, ANpreplant, and control treatments were 0.94, 0.86 and 0.20 g pot-1, respectively, suggesting that in the presence of the growing plants the release of N from DCODER had not been restricted. Furthermore, soil NO3-N levels in the bare soil plots of the field experiment were significantly higher in D-CODER (38.1 and 6.8 mg kg-1 on November and March) in comparison to ANpreplant (26.3 and 5.1 mg kg-1 on Nov. and March) treatments, suggesting that N from D-CODER was better protected from leaching. In the absence of growing plants, D-CODER provided some protection of N at least until 65 DAFA. In cultivated soils, it seemed less effective, particularly if the risk of nitrate leaching persisted for a long period of time. In these situations, a split application of N was a better strategy.